2010
DOI: 10.1001/archgenpsychiatry.2010.78
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Clusterin Concentration With Severity, Pathology, and Progression in Alzheimer Disease

Abstract: Context Blood-based analytes as indicators of pathological processes in Alzheimer's disease (AD). Objective Combined proteomic and neuroimaging approach to identify plasma proteins associated with AD pathology. Design Discovery-phase proteomic experiments to identify plasma proteins associated with correlates of AD pathology including evidence of atrophy using neuroimaging and more rapid clinical progression, followed by replication using quantitative immunoassay. Extension studies in older non-demented hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
332
7
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 363 publications
(372 citation statements)
references
References 46 publications
(55 reference statements)
28
332
7
5
Order By: Relevance
“…Carbonyl reductase is elevated in hippocampi of 3xTg‐AD mice, which have markedly elevated levels of protein carbonylation (Shen et al ., 2015). Clusterin (ApoJ) polymorphism is associated with AD (Lambert et al ., 2009), and its circulating levels predict AD progression (Thambisetty et al ., 2010). Other apolipoproteins are also strongly linked to AD risk: ApoD catalyzes reduction of peroxidized lipids and its levels increase with age and AD, while ApoE has allele‐specific effects on Aβ levels and AD risk (Tai et al ., 2013; Dassati et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Carbonyl reductase is elevated in hippocampi of 3xTg‐AD mice, which have markedly elevated levels of protein carbonylation (Shen et al ., 2015). Clusterin (ApoJ) polymorphism is associated with AD (Lambert et al ., 2009), and its circulating levels predict AD progression (Thambisetty et al ., 2010). Other apolipoproteins are also strongly linked to AD risk: ApoD catalyzes reduction of peroxidized lipids and its levels increase with age and AD, while ApoE has allele‐specific effects on Aβ levels and AD risk (Tai et al ., 2013; Dassati et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CLU was reported to be present in amyloid plaques (Giannakopoulos et al 1998). In addition, recent studies have revealed that the concentration of CLU in the CSF and plasma of AD patients is significantly elevated (Sihlbom et al 2008;Thambisetty et al 2010). Interestingly, as a chaperone protein, CLU has been proven to interact with Ab peptides and this interaction plays an important role in Ab aggregation, toxicity and clearance (Baig et al 2012;DeMattos et al 2002;Narayan et al 2012;Yerbury et al 2007).…”
Section: Clusterinmentioning
confidence: 99%
“…Later, a systematic review and meta-analysis in 2012 by Koyama et al [31] concluded that plasma A␤ 42 :A␤ 40 ratio may predict development of AD, however, significant heterogeneity in the meta-analysis underlines the need for substantial further investigation of plasma A␤ levels as a preclinical biomarker. Thambisetty et al have identified plasma clusterin as a potential biomarker for AD [32] and present data that suggests that plasma clusterin is associated with rate of atrophy in MCI [33].…”
Section: Introductionmentioning
confidence: 61%